Analysing women entrepreneurial empowerment challenges in South Africa: A systematic literature review - Utete, Reward; Mkhwanazi, Sinqobile Joseph (Edelweiss Applied Science and Technology, 2025)
Although women entrepreneurship is indispensable to ameliorate the social and economic development of countries around the globe, in South Africa, only accounts for 19,4% of business owners. Women entrepreneurs still face taxing times as they bear the brunt of unparalleled constraints, which are predominantly linked to gender-related biases. While the issue of women employment has been extensively researched, women entrepreneurship is empirically inconclusive, fragmented, and theoretically limited, leaving the subject underexplored. It is prudent not to cede further unremitting inequality space. Hence, the overarching purpose of this study is to investigate the constraints women entrepreneurship face in South Africa. The review integrates the burgeoning literature to investigate the personal complexities faced by women entrepreneurs in South Africa and to explicate the external impediments encountered by women entrepreneurs in South Africa. The study used a systematic literature review of the available literature from 75 studies over the period 2013–2023 to scrutinise the challenges associated with women entrepreneurship. The study used the PRISMA strategy to search Scopus, Web of Science, and Google Scholar databases. The findings also revealed various personal and external challenges encountered by women entrepreneurs. The study provides both theoretical and practical implications.